Effects of Grass Silage Additive Type and Barley Grain Preservation Method on Rumen Fermentation, Microbial Community and Milk Production of Dairy Cows - Rinne, Marketta; Franco, Marcia; Tapio, Ilma; Stefański, Tomasz; Bayat, Ali-Reza; Mäntysaari, Päivi (MDPI AG, 2022)
Grass was ensiled using an acid-based additive (AS) or homofermentative lactic acid bacteria (IS). In addition, barley grain was either dried (DB) or crimped and ensiled (EB). The feeds were fed as total mixed rations (TMR) in a 2 × 2 factorial arrangement to 16 Nordic Red dairy cows in four replicated Latin squares. The differences in the fermentation quality of the two grass silages were unexpectedly small. Dry matter intake was higher (p < 0.01) for cows fed AS than those fed IS but was not affected by barley preservation method. Ruminal molar proportion of butyrate tended to be higher in cows fed AS rather than IS (p < 0.10) in expense of acetate (p < 0.05). Barley preservation method did not affect rumen fermentation but modulated rumen bacterial community composition. Milk production was not affected by silage additive but tended (p < 0.10) to be higher (39.6 vs. 39.0 kg/d) for cows fed DB rather than EB. However, barley type did not affect energy corrected milk yield due to a tendency (p < 0.10) for higher milk fat content of cows fed EB rather than DB. Milk fat yield tended (p < 0.10) to be higher for AS-fed cows than IS-fed cows, and milk protein yield was higher for cows receiving DB rather than EB. The AS resulted in more aerobically stable TMR than IS and a minor advantage was found for DB compared to EB.
Keywords: säilörehu; säilöntä; säilöntäaineet; maidontuotanto (kotieläintuotanto); maitohappobakteerit; maitohappokäyminen; muurahaishappo; vilja; mikrobisto; aerobic stability; crimping; ensiled grain; formic acid; grain preservation; high-moisture grain; lactic acid bacteria inoculant; rumen microbiome; silage fermentation; säilörehu; säilöntä; säilöntäaineet; maidontuotanto (kotieläintuotanto); maitohappobakteerit; maitohappokäyminen; muurahaishappo; vilja; mikrobisto; aerobic stability; crimping; ensiled grain; formic acid; grain preservation; high-moisture grain; lactic acid bacteria inoculant; rumen microbiome; silage fermentation